2022-LBA-414-ESGO Preliminary clinical outcome of ADP-A2M4CD8, a next-generation autologous T-cell receptor T-cell therapy, in patients with advanced epithelial ovarian cancer. (27th October 2022) - Moore, Kathleen; Asch, Adam; Moreno, Victor; Calvo, Emiliano; Butler, Marcus; Zugazagoitia, Jon; Hong, David; Galal, Ahmed; Ostios, Lorena; de Miguel, Maria; Lin, Quan; Annareddy, Thejo; et al.
Abstract : Introduction: ADP-A2M4CD8, a next-generation specific peptide enhanced affinity receptor (SPEAR) T-cell therapy supplemented with a CD8α co-receptor, is being evaluated in the Phase 1 SURPASS trial (NCT04044859 ) in multiple solid tumours, including ovarian cancer. Promising anti-tumour activity, including a 36% overall response rate (1 complete response [CR], 7 partial responses [PR] in 22 evaluable patients; 2 August 2021 data cut-off) and a favourable benefit to risk profile were reported. 1 We report preliminary anti-tumour activity in ovarian cancer and updated safety in all tumours. Methods: SURPASS is a first-in-human trial evaluating ADP-A2M4CD8 using a modified 3+3 design, with 2 dose cohorts and an expansion cohort. 1 T-cells are collected by leukapheresis, transduced, and infused into the patient after lymphodepletion. Eligible patients express human leukocyte antigen A*02 with melanoma-associated antigen (MAGE)-A4-positive tumours. Patients with ovarian cancer must have received platinum-based chemotherapy and progressed ≤12 months post platinum therapy. Results: As of 1 August 2022, 14 patients with ovarian cancer had received 1.14–9.95×10 9 transduced T-cells. Median age was 59 years (range, 40–75); median number of prior systemic therapy regimens was 4 (range, 2–8); median MAGE-A4 expression H-score was 237.5 (range, 95–300). Adverse events in the overall population were consistent with lymphodepletion chemotherapy or cellular therapy; similar safety results were seen in the ovarian cancer subgroup ( table 1 ). There was 1 Grade 5 cytokine release syndrome. Best overall responses were 1 CR, 4 PR, 6 stable disease (SD), 2 progressive disease and 1 not evaluable, giving a 36% overall response rate and a 79% disease control rate (CR+PR+SD, figure 1 ). Conclusions: ADP-A2M4CD8 SPEAR T-cell therapy showed preliminary anti-tumour activity in heavily pre-treated patients with MAGE-A4+ advanced ovarian cancer, with tolerable emerging safety results. The trial now includes an anti-programmed death-ligand 1 combination treatment cohort. 1. Hong DS, et al. Ann Oncol. 2021;32(suppl5):540P.